What Opportunities For Storytelling Might Near-future Technologies Offer Creatives, And How Might Personal Data Affect This? - Strickland, J W (2022)
A common feature of storytelling, at least when it comes to a western, and classical perspective, is that of linearity. Stories often have a single path through them that the content of the story, the Fabula, is arranged along, with this arrangement of the content of the story, the Syuzhet, often being dictated by a single authorial voice. However, a rise in technology and an audience’s willingness to experience new storytelling methods has helped give rise to more experimentation, leading to the popularisation of audience-controlled linearity and interactive storytelling. There can be tension within this way of telling stories as it is commonly believed that in order to increase the interactive quality of a story you have to reduce the quality of the narrative, with some storytellers and researchers approaching narrative and interactivity as opposing forces. I believe that, by doing this, researchers and artists are accidentally limiting the scope of the combinations of Narrative and Interactivity they consider when researching these qualities of storytelling experiences. Narrative and Interactivity are neutral and complex features that can be mediated in different ways throughout a storytelling experience to create enjoyment in an audience, one of the main aims of most stories. Perhaps the multi-faceted nature of enjoyment has made reliably researching it seem difficult, futile, or even perhaps unscientific in the past, but using Roth’s (2015) battery of experimentally valid enjoyment questionnaires allows me to examine the enjoyment elicited in responses to an interactive narrative experience in an experimentally valid and appropriately detailed way. This means that I should be able to derive which quantities and qualities of interactivity and narrative create or hinder the creation of not just enjoyment in an audience, but specific facets and flavours of audience enjoyment. In order to test this hypothesis I had to build an interactive storytelling experience that could vary its amount of Narrative or Interactivity, and it became apparent while doing this that the system that runs this, a branching narrative that presented different video clips depending on audience responses, could also be used to run the research itself, not just deliver the narrative content of the research experience. Using this system, and taking inspiration from my experience with making interactive digital theatre and using magician’s crowd control techniques, such as the Equivoque Force or Barnum Statements, an automated researcher was created to help brief the participants, calibrate the audience behaviour data tracking system, and deliver quantitative and qualitative data collection procedures to the audience. This researcher felt lifelike without the use of complicated AI or machine learning by using a clever mix of simple narrative path systems and a careful anticipation of likely participant responses. The effectiveness of this sort of automated researcher was also investigated as part of this thesis. I found: • Various new methodologies that have wide uses for different researchers, including the automated research assistant and a way of analysing and comparing digital theatre experiences, called a Dramatography, as well as continued evidence for the use of a Performance Led Research and Rapid Iterative Prototyping a valuable methodology for examining these sorts of creative research questions. • In spite of the theory concerning the balance of Interactivity and Narrative, I found that a narratively rich and meaningfully interactive experience is achievable via a creative, low- resource methodology, that a minimal use of easy-to-measure audience behaviour data is required to create the feeling of meaningful interactivity and liveness, and that the type of audience behaviour data used to create that feeling didn’t have a significant effect on audience enjoyment. • That a majority of participants had positive things to say about the automated research assistant and found the experience of undergoing the research user-friendly in spite of the lack of a human researcher, meaning that a scalable and on-demand research methodology for both complex quantitative and qualitative data collection, with a recognisably human face, is possible.